The development of Couple HOPES: a guided online intervention for PTSD and relationship satisfaction enhancement. Issue 1 (1st January 2021) - Monson, Candice M.; Fitzpatrick, Skye; Wagner, Anne C.; Valela, Robert; Whitfield, Kristen M.; Varma, Sonya; Landy, Meredith S. H.; Di Bartolomeo, Alyssa; Crenshaw, Alexander O.; Fulham, Lindsay; Morland, Leslie; Knopp, Kayla; et al.
ABSTRACT: Background : Couple HOPES (Helping Overcome PTSD and Enhance Satisfaction) was created to help overcome a range of barriers to accessing psychotherapy for posttraumatic stress disorder (PTSD) and commonly associated intimate relationship problems. Objective : Couple HOPES is a guided, online self-help intervention adapted from Cognitive-Behavioural Conjoint Therapy for PTSD that aims to improve PTSD and enhance relationship satisfaction. Method/Results : This paper describes the processes and principles used to develop the Couple HOPES intervention platform as well as the coaching model and manual used to promote engagement and adherence to the intervention. Conclusions : Current research and future directions in testing Couple HOPES are outlined. HIGHLIGHTS: Couple HOPES is a guided, online self-help intervention adapted from Cognitive-Behavioural Conjoint Therapy for PTSD. It was created to overcome the many barriers to established in-person evidence-based psychotherapies.